2012
DOI: 10.1105/tpc.112.102012
|View full text |Cite
|
Sign up to set email alerts
|

Ribulose-1,5-Bis-Phosphate Carboxylase/Oxygenase Accumulation Factor1 Is Required for Holoenzyme Assembly in Maize

Abstract: Most life is ultimately sustained by photosynthesis and its rate-limiting carbon fixing enzyme, ribulose-1,5-bis-phosphate carboxylase/oxygenase (Rubisco). Although the structurally comparable cyanobacterial Rubisco is amenable to in vitro assembly, the higher plant enzyme has been refractory to such manipulation due to poor understanding of its assembly pathway. Here, we report the identification of a chloroplast protein required for Rubisco accumulation in maize (Zea mays), RUBISCO ACCUMULATION FACTOR1 (RAF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
133
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(146 citation statements)
references
References 67 publications
10
133
2
1
Order By: Relevance
“…However, the results showed that rbcL transcripts were not increased relative to the wild type in M cell RNA prepared from RBCS-BSD2, signifying that the increased rbcL transcript phenotype of bsd2 is likely a pleiotropic effect of the lack of Rubisco and not the effect of missing BSD2 in the M. The same phenomenon is seen in the maize raf1 mutant, which is blocked at a similar step in Rubisco assembly to bsd2 (Feiz et al, 2012). The function of BSD2 in the M remains unclear.…”
Section: Pepc-bsd2 Complemented Lines Accumulate Reduced Bsd2 In the mentioning
confidence: 61%
See 1 more Smart Citation
“…However, the results showed that rbcL transcripts were not increased relative to the wild type in M cell RNA prepared from RBCS-BSD2, signifying that the increased rbcL transcript phenotype of bsd2 is likely a pleiotropic effect of the lack of Rubisco and not the effect of missing BSD2 in the M. The same phenomenon is seen in the maize raf1 mutant, which is blocked at a similar step in Rubisco assembly to bsd2 (Feiz et al, 2012). The function of BSD2 in the M remains unclear.…”
Section: Pepc-bsd2 Complemented Lines Accumulate Reduced Bsd2 In the mentioning
confidence: 61%
“…Based on available evidence, BSD2 was proposed to interact with the large subunit (LS) of Rubisco to facilitate its translation and/or folding (Brutnell et al, 1999). Subsequent work in maize showed that BSD2 likely interacts with nascent LS and/or newly imported small subunit as well as other assembly factors (RAF1 and RAF2) to assemble the Rubisco holoenzyme (Feiz et al, 2012(Feiz et al, , 2014. More limited data are consistent with analogous roles in Nicotiana benthamiana (Wostrikoff and Stern, 2007) and Chlamydomonas reinhardtii (Doron et al, 2014).…”
mentioning
confidence: 77%
“…Although the OR proteins carry a DnaJ cysteine-rich zinc figure domain, they are not molecular chaperones due to the lack of the DnaJ-like defining J domain. A member of the specific OR group proteins is BUNDLE SHEATH DE-FECTIVE2 (BSD2), which affects Rubisco accumulation and is believed to function via direct interaction with the polypeptide substrates for Rubisco assembly (35,36). Accordingly, the physical association of OR with PSY might promote the proper folding of PSY to enhance its stability and activity.…”
Section: Or Proteins Function As the Major Regulators Of Psy Protein mentioning
confidence: 99%
“…For example, the cyanobacterial RbcX gene, which is co-transcribed with the rbcL and rbcS genes in the rbcLXS operon (Saschenbrecker et al, 2007), stabilizes the RbcL as a dimer and facilitates the core assembly of an octagonal structure (Liu et al, 2010). Similarly, in the photosynthetic eukaryote Zea mays, Raf1 is an important specific factor that is required for post-translational holoenzyme assembly (Feiz et al, 2012). Another potential factor that is required for Rubisco expression is the bundle sheath defective-2 (BSD2) protein, which was initially identified in maize (Brutnell et al, 1999).…”
Section: Introductionmentioning
confidence: 99%